The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s2236-89062014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização morfológica e molecular de fungos micorrízicos arbusculares isolados de áreas de mineração de gesso, Araripina, PE, Brasil

Abstract: Foi determinada a ocorrência de espécies de fungos micorrízicos arbusculares (FMA) em áreas nativa (AN) e impactada (AI) pela mineração de gesso em Araripina, PE, Brasil, utilizando como culturas-armadilha: sorgo e amendoim. Os esporos de FMA foram caracterizados morfologicamente para identificação ao nível de espécie. DNA foi extraído de esporos para caracterização molecular a partir de sequencias da região ITS. No estudo molecular foram identificados três gêneros e quatro espécies (Funneliformis mosseae, Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Plant establishment and development are associated with mycorrhizal. Mycorrhizal plants have more efficient nutritional strategies than non-mycorrhizal plants, benefiting survival under stress (Mergulhão et al, 2014).…”
Section: Genotypesmentioning
confidence: 99%
“…Plant establishment and development are associated with mycorrhizal. Mycorrhizal plants have more efficient nutritional strategies than non-mycorrhizal plants, benefiting survival under stress (Mergulhão et al, 2014).…”
Section: Genotypesmentioning
confidence: 99%
“…These authors observed an increase in spore density in areas subjected to strong water stress at the sampling time. Mergulhão et al (2014) also stated that mycorrhizal symbiosis is a plant strategy to overcome biotic and abiotic stresses, increasing spore density under adverse conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first study to include intra-radical spores as part of the quantification of mycorrhizal root structures. Although spores have been recognized as important propagules for the survival of AM fungi (Smith and Read, 2008) and many species regularly form spores inside roots (Mergulhão et al, 2014;Sieverding et al, 2014), they have usually not been considered or have been quantified erroneously as vesicles (Giovanetti and Mosse, 1980;McGonigle et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…An intersection was considered colonized if intraradical hyphae, arbuscules, vesicles and/or spores were present. Many studies that have analyzed mycorrhizal colonization have not reported the presence of spores inside roots; however, in this study, we also considered these propagules since some AMF species sporulate within roots (Mergulhão et al, 2014;Sieverding et al, 2014).…”
Section: Mycorrhizal Colonization Ratementioning
confidence: 99%